Compression Test on Cold-Formed Steel Built-up Back-to-Back Channels Stub Columns - Ting, Chui Huon Tina; Lau, Hieng Ho (Trans Tech Publications Inc, 2011)
Built-up sections are used to resist load induced in a structure when a single section is not sufficient to carry the design load for example roof trusses. In current North American Specification, the provision has been substantially taken from research in hot-rolled built-up members connected with bolts or welds [1]. The aim of this paper is to investigate on built-up back-to-back channels stub columns experimentally and theoretically using Effective Width Method and Direct Strength Method. Compression test was performed on 5 lipped channel and 5 back-to-back channels stub columns fabricated from cold-formed steel sheets of 1.2mm thicknesses. The test results indicated that local buckling is the dominant failure modes of stub columns. Therefore, Effective Width Method predicts the capacity of stub columns compared to Direct Strength Method. When compared to the average test results, results based on EWM are 5% higher while results based on DSM are 12% higher for stub column.